Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan Di Kelurahan Cigugur Tengah - Kiranie, Ditha; Prihadi, Dana; Suryaman, Warman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Today in the era of globalization, it is important for organizations to improve employee performance so that the organization can develop and achieve its goals. The success of achieving these organizational goals can be achieved by improving the quality of human resources within the organization. In an organization with various kinds of individuals as employees, it often produces different qualities. The existence of these differences is caused by several factors including the style of leadership. The indicator of the success of a leader is the success of his employees in completing tasks and carrying out the responsibilities given, and this cannot be separated from the motivation that has been given to employees, of course most of the motivation to work more productively lies in the employees themselves. This study aims to determine the effect of leadership style on employee performance in Cigugur Tengah Village. The method used is a quantitative approach with the population and sample in this study all employees in the Cigugur Tengah Village, Cimahi City. The data analysis technique used in this study is a simple linear regression analysis technique. A simple linear regression analysis technique was used to test the effect of leadership style on performance in Cigugur Tengah Village.The results of the study show that there is a significance value of (0.070> 0.050) and the calculated t value is smaller than t table (2.029 <2.228) so that Leadership Style has no effect on employee performance.